2019
DOI: 10.1038/s41431-019-0530-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlations between pain phenotypes and depression and neuroticism

Abstract: Correlations between pain phenotypes and psychiatric traits such as depression and the personality trait of neuroticism are not fully understood. In this study, we estimated the genetic correlations of eight pain phenotypes (defined by the UK Biobank, n = 151,922-226,683) with depressive symptoms, major depressive disorders and neuroticism using the the crosstrait linkage disequilibrium score regression (LDSC) method integrated in the LD Hub. We also used the LDSC software to calculate the genetic correlations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
46
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 47 publications
8
46
0
1
Order By: Relevance
“…The SNP heritability of neck or shoulder pain was 0.11. This is similar to that of back pain (0.11), greater than knee pain (0.08), and less than: hip pain (0.12), stomach or abdominal pain (0.14), headache (0.21), facial pain (0.24), and pain all over the body (0.31) (51). Further, the genetic correlation matrix among 8 pain phenotypes in the UK Biobank showed that the neck or shoulder pain and back pain shared the highest genetic correlation (rg = 0.83) (51).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The SNP heritability of neck or shoulder pain was 0.11. This is similar to that of back pain (0.11), greater than knee pain (0.08), and less than: hip pain (0.12), stomach or abdominal pain (0.14), headache (0.21), facial pain (0.24), and pain all over the body (0.31) (51). Further, the genetic correlation matrix among 8 pain phenotypes in the UK Biobank showed that the neck or shoulder pain and back pain shared the highest genetic correlation (rg = 0.83) (51).…”
Section: Discussionsupporting
confidence: 69%
“…The genetic correlation analysis results were perhaps to be expected. Like knee pain and back pain, which have been shown to be positively correlated with depression and neuroticism (51), neck or shoulder pain was correlated genetically and positively with some mental health and personality phenotypes. We also identified that neck or shoulder pain was genetically and negatively correlated with the age at which they have their first child, college completion, and years of schooling.…”
Section: Discussionmentioning
confidence: 99%
“…Further, precision medicine approaches need such a better understanding of the precise relationship between genes and phenotype to reveal underlying biological mechanisms. Finally, the discovery of novel subclasses may eventually translate into clinical care [24]. Recent studies have shown progress in the genetic correlations between pain phenotypes and psychiatric traits or using RNA sequence analysis on chondrocytes from osteoarthritis patients [25].…”
Section: Introductionmentioning
confidence: 99%
“…Also, we used common SNPs to estimate the heritability of CWP, so the contribution of other variants in the heritability estimated remains unknown. Other musculoskeletal pain assessed in UKB (knee, hip, back, and neck or shoulder pain) exhibited SNP-heritability on the liability scale in the range 0.08–0.12[62], and these estimates are considerably lower than our estimate for CWP, suggesting CWP is a trait of high genetic influence.…”
Section: Discussionmentioning
confidence: 67%
“…Second, we observed a tendency towards non-significance for the COMT locus in the sensitivity GWAS due to the exclusion of participants with non-musculoskeletal pain from the control group suggesting that COMT predisposes to chronic pain in general. Finally, genetic factors underlying chronic pain and psychiatric co-morbidity (e.g., depression and neuroticism) are known to be shared[62]. However, previous GWAS on chronic pain[29, 63, 64], depression[65] and neuroticism[66] have failed to detect an association with COMT .…”
Section: Discussionmentioning
confidence: 99%